Tube Gastropexy for the Management of Gastric Dilatation Volvulus in a Dog - Bapu, Sabarish; Dsouza, Nitin JD (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Gastric Dilatation Volvulus (GDV) is an acute condition with mortality rate of 20% to 45% in treated animals, (Evans and Adams, 2010). Dogs fed a large volume of food per meal were at increased risk of developing GDV, (Raghavan et al., 2004). Male gender, being under weight, eating rapidly, gastric motility disorders, stress are the predisposing factors for GDV, (Raghavan et al., 2006). This report describes the successful medical and surgical management of GDV and splenic torsion in a German Sheperd Dog.